2020
DOI: 10.1002/pep2.24188
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and antibiofilm efficacy of synthetic polymyxin‐mimetic lipopeptides

Abstract: The increasing emergence of multidrug‐resistant bacteria is a huge problem to society providing significant risks to public health. This has been further escalated by a decline in the clinical translation of new antibacterial drug classes since the 1980s. In this article, we describe the synthesis, antibacterial/antibiofilm activity and in vitro toxicity of synthetic low molecular weight lipopeptides mimetics of polymyxin. C12‐KTKCKFLKKC‐NH2 and C14‐KTKCKFLKKC‐NH2 lipopeptides demonstrated activity against bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…A biofilm is an aggregation of one or more species of microorganisms adhered to a surface, as compared to planktonic bacteria, which exist as individual organisms [20] , [51] . Biofilm-forming bacteria are reported to be 100–1000 times more resistant to antibiotics than planktonic bacteria [13] , [14] . In this study, biofilm inhibition and reduction-crystal violet assay suggested that all the tested antibiotics at 8, 4, 2, 1 and 0.5 µg/mL concentrations were significantly able to decrease P. aeruginosa biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A biofilm is an aggregation of one or more species of microorganisms adhered to a surface, as compared to planktonic bacteria, which exist as individual organisms [20] , [51] . Biofilm-forming bacteria are reported to be 100–1000 times more resistant to antibiotics than planktonic bacteria [13] , [14] . In this study, biofilm inhibition and reduction-crystal violet assay suggested that all the tested antibiotics at 8, 4, 2, 1 and 0.5 µg/mL concentrations were significantly able to decrease P. aeruginosa biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to antibiotics is approximately 1000 fold more in attached bacteria than planktonic cells because of an increase in mutation rates, upregulation of efflux pumps, decrease in metabolic activity, and other physical reasons [13] . The resistance mechanism is unique to biofilm-encapsulated bacteria as the biofilm phenotype provides a protective advantage [13] , [14] . Bacteria alter gene expression during biofilm development adaption, encouraging phenotypically different behavior compared to planktonic counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of biofilm inhibition was estimated using the formulas shown below. The experiment was carried out in triplicate ( 18 , 19 , 22 , 23 ). …”
Section: Methodsmentioning
confidence: 99%
“…The adhesion of bacteria on the catheter surface is governed by reversible weak forces such as Van der Waals or electrostatic attraction forces and then by the formation of irreversible strong forces like covalent bonds 6 . Bacteria attached to the biomaterial surface leads to subsequent colonization and eventually provoke the formation of biofilms 7 9 as illustrated in Fig. 1 .…”
Section: Introductionmentioning
confidence: 99%